2022
DOI: 10.1088/1742-6596/2157/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hue Saturation Value (HSV) color feature in kidney histology image

Abstract: The kidney is organ that plays an important role in the body’s metabolism, especially the process of filtration and reabsorption of food waste. Currently the determination of kidney parts through kidney histology is still done manually by experts based on experience and knowledge. Therefore, to make it easier to determine the parts of the kidney, a histological image segmentation of the kidney was carried out. In the segmentation process, it is necessary to extract the color features of the parts of the kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…According to the findings of the sensitivity analysis, it can be concluded that the S and H were the most and least influential factors, corresponding to predict TSS and pH for both models. Some published articles also reported similar results on the importance of colour channels in object detection [89,90].…”
Section: Sensitivity Analysis Of Colour Spacessupporting
confidence: 53%
“…According to the findings of the sensitivity analysis, it can be concluded that the S and H were the most and least influential factors, corresponding to predict TSS and pH for both models. Some published articles also reported similar results on the importance of colour channels in object detection [89,90].…”
Section: Sensitivity Analysis Of Colour Spacessupporting
confidence: 53%
“…This model finds wide applications across various scientific and technological domains, including medical research. For instance, it has been employed in the analysis of kidney histology images [ 29 ], in the study of patients undergoing treatment for ischemic heart disease to assess tongue appearance [ 30 ], and as a foundational approach for comprehensive image analysis in medicine [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the existing color systems, including RGB (Red, Green, Blue), HSV/HSB (Hue, Saturation, Value / Hue, Saturation, Brightness), and CIELAB (International Commission on Illumination), the HSV/HSB model was selected for our analysis. The HSV color space is extensively applied in image retrieval contexts, aligns with human visual sensation, and enables the robust characterization of image content [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Saturation/Value mean for an HSV image is calculated by simply taking the maximum and minimum value of saturation/value of an image [60]. The basic value of skewness can be estimated by equation ( 6) below.…”
Section: Skewnessmentioning
confidence: 99%